PID damper design for wide‐area power systems considering time delays. (10th August 2020) - Qi, Jun; Li, Yuanchao; Ou, Linlin
Summary: Wide‐area damping control is able to improve the stability of inter‐connected power systems in case of low‐frequency oscillations. Nevertheless, the damping effect is closely related to the time delay of wide‐area control loops. The application potential of proportional‐integral‐derivative (PID) damper is explored in wide‐area power system damping control. First, the relative residue index based on dominant oscillation modes is employed to determine a suitable control loop. Then, the PID stability space is calculated numerically based on extended Hermite–Biehler Theorem. Finally, the damping‐robustness balance principle is discussed in the PID parameters selection. The proposed PID damper is tested by supplementing the generator excitation control in the two‐area four‐machine power system and the static var compensator control in the 16‐machine 68‐bus power system. Simulation results confirm that it is feasible to design a PID damper for the control loop with a larger relative residue index. The designed PID damper is able to enhance power system stability by inhibiting low‐frequency oscillations under considerable time delays, and it is robust to the changes of system operation state and time delay.